DFT combined with XANES to investigate the sulfur fixation mechanisms of H2S on different CaO surfaces. (1st November 2022) - Shi, Tong; Guo, Huiqing; Liu, Yue; Wang, Long; Lei, Yanqiu; Hao, Haigang; Liu, Fenrong
Graphical abstract: H2 S was detected to release after 300°C during the pyrolysis of Erdos (ED) coal with high inorganic sulfur content under Ar atmosphere, while CaO can obviously fix sulfur above 700°C. S K-edge XANES spectrum can prove that CaO fixing sulfur mainly generates CaS. The possible sulfur-fixation mechanisms can be described by DFT method. Highlights: CaO possesses the obvious sulfur fixation ability above 700 °C by the experimental results analysis. The CaO perfect face can fix H2 S about 700 °C and form CaS. CaS (S K-edge XANES spectrum proved) and clean energy H2 are generated above 400 °C on the surface of the O vacancies. O is the active site on CaO (0 0 1), and the O vacancy is the electron-donating system. Abstract: In this study, Erdos (ED) coal with high inorganic sulfur content was selected to investigate the absorbed effects of H2 S on the perfect or defective surfaces of CaO (0 0 1). Pyrolysis connected with gas chromatography (Py-GC) was used to analyze H2 S release behavior during coal pyrolysis. S K-edge XANES spectrum can prove that CaO fixing sulfur mainly generates CaS. The O vacancy of CaO possesses the best adsorption effect of H2 S. Through the electronic structure and orbital analysis, O atom can be confirmed to the active site on the surfaces of CaO (0 0 1), and the O vacancy belongs to a strong electron-donating system. Different paths of H2 S fixation can undergo on both perfect surface and O vacancy of CaO. After 700 °C, the most possible paths would happen and generate CaS and clean energy H2 on the surface of the O vacancies. However, it is impossible for Ca vacancies to be generated and to further fix H2 S during pyrolysis under inert atmosphere. These calculated results are very consistent with these experimental results. Thus, this study would provide theoretical support for the sulfur fixation mechanisms on the surface of CaO (0 0 1) and for the subsequent improvement of the CaO sulfur fixation agent.